Diachronic metamorphic and structural evolution of the Connecticut Valley–Gaspé trough, Northern Appalachians. (21st October 2019) - Perrot, Morgann; Tremblay, Alain; Ruffet, Gilles; Labrousse, Loic; Gervais, Félix; Caroir, Fabien
Abstract: The Connecticut Valley–Gaspé (CVG) trough represents a major, orogen‐scale Silurian–Devonian basin of the Northern Appalachians. From Gaspé Peninsula to southern New England, the CVG trough has experienced a contrasting metamorphic and structural evolution during the Acadian orogeny. Along its strike, the CVG trough is characterized by increasing strain and polyphase structures, and by variations in the intensity of regional metamorphism and contrasting abundance of c . 390–370 Ma granitic intrusions. In southern Quebec and northern Vermont, a series of NW–SE transects across the CVG trough have been studied in order to better understand these along‐strike variations. Detailed structural analyses, combined with phase equilibria modelling, Raman spectrometry, and muscovite 40 Ar/ 39 Ar dating highlight a progressive and incremental deformation involving south–north variation in the timing of metamorphism. Deformation evolves from a D1 crustal thickening event which originates in Vermont and progresses to southern Québec where it peaked at 0.6 GPa/380°C at c . 375 Ma. This was followed by a D2 event associated with continuous burial in Vermont from 378 to 355 Ma, which produced peak metamorphic conditions of 0.85 GPa/380°C and exhumation in Quebec from 368 to 360 Ma. The D3 compressional exhumation event also evolved from south to north from 345 to 335 Ma. D1 to D3 deformation events form part of a continuum with an along‐strike propagation rate of 50 km/Ma During D1, the burial depth varied by more than 15 km between southern Quebec and Vermont, and this can be attributed to the occurrence of a major crustal indenter, the Bronson Hill Arc massif, in the New England segment of the Acadian collision zone.